Pertumbuhan Kebutuhan Pondok Pesantren Menggunakan Graph - Rosida, Rizka Birthdayani Rodliata; Hanifah, Aulia Wahyu; Adzkiya, Faaula Dzurriyatul; Yaqin, M. Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Islamic boarding school is one of the educational institutions in Indonesia as a means of learning Islam. Every Islamic boarding school in Indonesia has a different growth. The growth in the needs of Islamic boarding schools is strongly influenced by the number of new students enrolling, so it is necessary to plan and analyze the growth of the needs of Islamic boarding schools as a determinant of planning for further handling. This study aims to determine the growth of existing facilities in the boarding school in the specified operational standards. The stages of this research are knowing the history of Islamic boarding schools to determine the initial formation until they become qualified boarding schools, then we can draw a chart using Graphs to see the growing needs of each period. In the calculation, the AHP (Analytical Hierarchy Process) method also has a role to analyze the value generated from the Graph calculation as a benchmark for each growth period, so as to produce growth charts of the needs of Islamic boarding schools in each period. From this research, it can be used to actualize further business architecture.